Estimation of strength properties of geopolymer concrete. (2021) - Bin Ahmed, Farabi; Biswas, Rajib Kumar; Abid Ahsan, Khan; Islam, Somaiya; Rahman, Md. Ridwanur
Abstract: Compressive and tensile strength are important parameters to know the quality of concrete. This study represents a method predicting the split tensile strength through the compressive strength (0 up to 65 MPa) of cube and cylinder specimens of concrete by polynomial regression analysis. The polynomial equation for both 7 and 28 days have been developed and cube compressive strength are adjusted by multiplying a factor 0.8. To formulate the model, experimental data have been gathered from various literatures. It is noticed that the geopolymer concrete split tensile and compressive strength ratio showed more nonlinearity than existing prediction models and the split tensile strength gaining rate is not so high in 7 days. It is also noticed that existing geopolymer concrete prediction models are good fit in 7 days than the 28 days and traditional prediction models are not also suitable for geopolymer concrete tensile strength prediction. The suggested equations are evaluated based on R 2, RMSE, MAPE, and IAE parameters and compared with other models.